Prevalence of skin disease in a population‐based sample of adults from five European countries. (1st May 2018) - Svensson, A.; Ofenloch, R.F.; Bruze, M.; Naldi, L.; Cazzaniga, S.; Elsner, P.; Goncalo, M.; Schuttelaar, M.‐L.A.; Diepgen, T.L.
Summary: This study is based on a survey carried out by investigators with an interest in the epidemiology of skin disease based in 5 different European countries (Germany, Italy, the Netherlands, Portugal and Sweden). Epidemiology is the 'who, when and where' of diseases, looking at who gets certain illnesses and why. This survey was designed to show the patterns of skin disease in these different regions. 12, 377 individuals aged between 18 and 74 years were given a questionnaire designed to record skin conditions during their lifetime, in the past year and in the past month. In order to ensure that this was valid, details of who had made the diagnosis and how the condition was treated were also gathered. The most common skin diseases reported over a patient's life time were warts (41.3%), acne (19.2%) and contact dermatitis (15.0%) followed by other forms of eczema and atopic dermatitis, other skin diseases and urticaria. In general, females were more commonly affected by skin diseases compared to males, except that skin cancer was commoner in males. Overall skin diseases were commoner in northern European countries (Germany, Netherlands and Sweden) than in the south of Europe (Italy & Spain). While in most countries dermatologists were usually consulted for diagnosis and treatment, in the Netherlands other doctors, including general practitioners, were often involved.